Performance level differences in swimming: A meta-analysis of passive drag force - Havriluk, R. (Research Quarterly for Exercise and Sport, 2004)
The streamline is a basic position for competitive swimming starts and turns and has been used in many studies on resistive forces. However, there is a wide variety of theoretical interpretations in these studies, leading to diverse and questionable conclusions. The purpose of this study was to determine performance level differences in the streamline position using a meta-analysis. Faster swimmers had a significantly lower coefficient of drag (C d ) than slower swimmers, ( M = .57, z = 4.30, p < .001, SE = .13, 95% CI = .32-.82) and, therefore, a more effective streamline position. The results support considering all the related variables in a study of passive drag and using the C d to discriminate between performance levels in swimming.